Kepemimpinan Kepala Sekolah dalam Penguatan Pendidikan Karakter di SMAN 1 Yogyakarta - Rani Putri Prihatin; Shobaihatul Khoiroh (Nusantara: Jurnal Pendidikan Indonesia, 2021)
The background of this research stems from the interest of researchers about the importance of the role of principal leadership in strengthening character education. This study aims to determine the type, role, and implementation of the character education strengthening program at SMAN 1 Yogyakarta. This research is a qualitative research taking place at SMAN 1 Yogyakarta. Methods of data collection are done by means of observation, interviews, and documentation. Data analysis techniques by transcript, coding, comparing and contrasting. Checking the validity of the data by means of triangulation of sources, triangulation of techniques, and triangulation of time. The results showed that: (1) the type of leadership applied by the principal is a type of democratic leadership where the principal always provides encouragement, motivation and innovation for teachers, employees and students to continue to excel and continue working. (2) The implementation of the character education strengthening program using the habituation and culture methods of 5S (Greetings, Smiles, Greetings, Polite, and Polite) character education strengthening programs are supported by school members so that the program has been implemented optimally. (3) the principal acts as an educator, manager, administrator, supervisor, leader, innovator and as a motivator.